Sosialisasi Anti Narkoba Sebagai Gerakan Melawan Narkoba Serta Membangun Kesadaran Untuk Generasi Sehat di SMAN 1 Kubu - Fhajri Ramadhan; Ani Mariza; Muhammad Reski; Muhammad Samah; Tia Stefani Saragi; Sevilla Saviola Puteri; Nadila Nur Sapitha; Intan Syahraini; Nurul Hasanah; Mei Rifandi (Lembaga Pengembangan Kinerja Dosen, 2024)
This socialization aims to raise awareness of SMAN 1 Kubu students in preventing drug abuse. With the knowledge provided, students at SMAN 1 Kubu can find out the history of drugs, the factors that cause drug abuse, examples of drug abuse cases, as well as the impacts and consequences of drug abuse. This outreach is a very important thing to do because it can build awareness to fight drugs. Riau University Kukerta students hope that this socialization can prevent and reduce cases of drug abuse in Indonesia.